Pengujian Dan Analisa Anti Komputer Forensik Menggunakan Shred Tool - Rahardjo, Budi; Pratama, I Putu Agus Eka (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 2 Agustus 2016, 2016)
Computer forensics and anti computer forensics are two opposing fields. Computer forensics is done by a computer forensics expert in order to obtain accurate data and evidence of cyber crime cases for investigation, while the anti-computer forensics conducted by the attacker to remove traces at once difficult computer forensics expert in performing its duties. For the attacker, the selection of anti-computer forensics tool that default on the target machine, more effective and faster than installing it first on the victim machine. For this reason the author chose shred as anti computer forensics applications on GNU / Linux machine. If anti forensic work, forensic experts would be difficult to perform computer forensics to data as evidence of cyber crime. This paper describes the anti-forensics performed by the attacker to remote machines GNU / Linux for cyber crime cases in a computer network. Anti forensic performed using shred the syslog file to remove traces of the crime at the same time make it difficult for the forensic process by computer forensics expert. Tests performed on three pieces of computer-based GNU / Linux on System Signals Lab intranet ITB. Each act as the target machine (server), firewall machine, and the machine attacker. Doing the anti computer forensics and computer forensics at the server machine. The test results are recorded and analyzed in order to then be deduced.
Keywords: Anti Forensik, Shred, GNU/Linux, Network